2019
DOI: 10.1155/2019/6173412
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture-Analgesia-Mediated Alleviation of Central Sensitization

Abstract: Pain can trigger central amplification called central sensitization, which ultimately results in hyperalgesia and/or allodynia. Many reports have showed acupuncture has an analgesic effect. We searched the related article on PubMed database and Cochrane database to discover central sensitization pathway in acupuncture analgesia. We summarized that acupuncture enhances the descending inhibitory effect and modulates the feeling of pain, thus modifying central sensitization. The possible mechanisms underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 168 publications
(168 reference statements)
2
55
0
1
Order By: Relevance
“…EA at body surface acupoints can inhibit visceral injury response at multiple nerve levels with the largest inhibitory effect on spinal dorsal horn [8]. EA can also significantly inhibit the expression of NMDA receptor 1 (NR1) [9] and NR2B receptors [10,11] in the spinal dorsal horn in relieving visceral hypersensitivity [12,13]. In recent years, it has been found that activation of spinal glial cells is a key factor in the occurrence and persistence of visceral hypersensitivity [14].…”
Section: Introductionmentioning
confidence: 99%
“…EA at body surface acupoints can inhibit visceral injury response at multiple nerve levels with the largest inhibitory effect on spinal dorsal horn [8]. EA can also significantly inhibit the expression of NMDA receptor 1 (NR1) [9] and NR2B receptors [10,11] in the spinal dorsal horn in relieving visceral hypersensitivity [12,13]. In recent years, it has been found that activation of spinal glial cells is a key factor in the occurrence and persistence of visceral hypersensitivity [14].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, so far, this study may be the first clinical trial study that aims to demonstrate the FC effect on AHZ infection with rigorous design and it may also be different from the reference therapy. However, it has gotten our attention that several existing Chinese literatures did report on fire needle and cupping technique to cure for HZ [12][13][14]16] but all of them did not take up a rigorous design trial and are lacking of sufficient evidence to prove FC treatment has a positive effect on AHZ.…”
Section: Discussionmentioning
confidence: 99%
“…Ancient TCM practitioners also found that the heat provided by fire needles can promote microcirculation in the lesion area through the regulation of cutaneous nerves, and it is particularly beneficial to the absorption of inflammation and metabolites [13]. Furthermore, the high temperature of fire needles can generate an effect that directly kills the microorganisms and achieves antiinflammatory outcomes [14]. Therefore, this trial is aiming along the same line as ancient TCM practitioners and to further provide the fact results in order to validate the analgesic effect on acute herpes zoster (AHZ) treated by trial group A (FC).…”
Section: Introductionmentioning
confidence: 99%
“…Vickers 34 2012 [13] RCT [19] 10.5 [17] 21.5 [17] 0 [12] Not assessed [16] 15.67 Trigkilidas 35 2010 [10] RCT [19] 4.5 [4] 14 [2] 0 [12] Not assessed [16] 10.50 Machado 36 2009 [8] RCT [19] 7.5 [10] 18.5 [10] 0 [12] Not assessed [16] 12.50 Keller 37 2007 [4] RCT [19] 4 [3] 14.5 [3] 2.5 [17] Not assessed [16] 10.33 Yuan 38 2008 [7] RCT [19] 9 [14] 16.5 [7] 0 [12] Not assessed [16] 12.50 Manheimer 39 2005 [3] RCT [19] 6 [7] 23.5 [18] 0 [12] Not assessed [16] 12.50 Ammendolia 40 2008 [7] RCT [19] 6.5 [8] 15 [4] 0 [12] Not assessed [16]…”
Section: Discussionmentioning
confidence: 99%
“…7 As a safe and acceptable form of acute analgesia, acupuncture can relieve the symptoms of LBP. [8][9][10] The analgesic mechanism of acupuncture is to stimulate sensory nerve endings, leading to the release of endogenous opioid hormones and other nonopioids in the brain and spinal cord, [11][12][13] which could block the transmission of nerve impulses and thereby relieve pain. 14 In the American College of Physicians guideline, six related SRs and RCTs about acupuncture were included on noninvasive treatments for LBP, the oldest of which was published in 2002.…”
Section: Introductionmentioning
confidence: 99%